Evaluation of umbilical cord complication and its relation with foetal outcome - Jeenwal, Aarti; Jharbade, Hemlata (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: There are numerous umbilical cord abnormalities ranging from false knots, which have no clinical significance, to vasa previa, which could cause foetal loss. With availability of more sophisticated prenatal ultrasound techniques, many can be detected early in utero, however many of these are not apparent till delivery. In this study primary objective was to study correlation of umbilical cord complications and foetal outcome. Authors also outlined available courses of action to avert their morbidity and mortality. Methods: Prospective case control study was conducted in Department of Obstetrics and Gynaecology of M.G.M. Medical College and M. Y. Hospitals, Indore. Antenatal women with more than 28 weeks gestation were included. 500 cases with cord abnormalities were followed till delivery and were compared to the 500 controls with normal cord findings. Data was recorded in predesigned coded case report forms and statistical analysis was performed. Results: Of all the cord complications studied nuchal cord was the commonest i.e. 66.2% followed by abnormal cord length 12.4%. Incidence of cord prolapse was 7.2%. Single umbilical artery, cord knot and abnormal umbilical artery flow were found in 4%, 1.38% and 0.68% respectively. Conclusions: The presence of nuchal cord per se is not found to be an indication of operative delivery. However, these cases require close intrapartum monitoring. Gross cord abnormality was associated with still birth, intra uterine growth restriction and intrapartum or immediate post-natal complication.